How extreme are flood peak distributions? A quasi-global analysis of daily discharge records - Zaerpour, Masoud; Papalexiou, Simon Michael; Pietroniro, Alain; Nazemi, Ali (Journal of Hydrology, 2024)
Keywords: Infolettre; Infolettre_Avril_2024

Toward an Operational Water Cycle Prediction System for the Great Lakes and St. Lawrence River - Durnford, Dorothy; Fortin, Vincent; Smith, Gregory C.; Archambault, B.; Deacu, Daniel; Dupont, Frédéric; Dyck, Sarah; Martinez, Y.; Klyszejko, Erika; MacKay, M.; Liu, L.; Pellerin, Pierre; et al. (Bulletin of the American Meteorological Society, 2017)
AbstractIn this time of a changing climate, it is important to know whether lake levels will rise, potentially causing flooding, or river flows will dry up during abnormally dry weather. The Great Lakes region is the largest freshwater lake system in the world. Moreover, agriculture, industry, commerce, and shipping are active in this densely populated region. Environment and Climate Change Canada (ECCC) recently implemented the Water Cycle Prediction System (WCPS) over the Great Lakes and St. Lawrence River watershed (WCPS-GLS version 1.0) following a decade of research and development. WCPS, a network of linked models, simulates the complete water cycle, following water as it moves from the atmosphere to the surface, through the river network and into lakes, and back to the atmosphere. Information concerning the water cycle is passed between the models. WCPS is the first short-to-medium-range prediction system of the complete water cycle to be run on an operational basis anywhere. It currently produces ...
MAG ID: 2766397048